KOŠARE – A SYMBOL OF MULTIPLE MEANING AND A NEW COMPONENT OF SERBIAN NATIONAL IDENTITY - Mirović Janković, Aleksandra (Political Review, 2025)
The paper points out that, in addition to its great historical, geopolitical and geostrategic significance, the Battle of Košare, fought during the NATO aggression against the Federal Republic of Yugoslavia (Serbia and Montenegro) in the spring of 1999, also has produced certain consequences in the field of identity for the Serbian people and state. In the first part, within the framework of the analysis of the military-historical context and socio-political consequences of the battles fought at Košare and Paštrik, the various strategic dimensions of the NATO military operation, which was labeled as a humanitarian military intervention, are critically examined, relying, among other things, on Noam Chomsky’s concept of “new militariy humanism”. It is shown that it was essentially a reflection of the decivilization process and a deep and destructive antihumanism, as well as a precursor to what is today called hybrid warfare. Then, in the second part of the researching, the focus of the analysis is precisely the symbolic-identity function of the Battle of Košare and the very concept of Košare. It first points out the different symbolic meaning attributed to the concept of Košare depending on the parties to the conflict, which is to say that there are Albanian and Serbian symbolisms of “Košare”. However, the research focuses on “Košare” as a Serbian national symbol that has its own narrower, but also certain broader dimensions. Considering that over the past quarter of a century the concept of Košare has acquired the status of a kind of symbol in the Serbian people and society, the starting point was the assumption that the process of establishing “Košare” as a significant component of Serbian national and cultural identity can already be marked. The goal is to determine the phase in which this process is. It will be shown that it has primarily been initiated from below, that is, by society itself, and initiatives from above have only recently become more visible. This is interpreted as an inverse process. According to the research findings, in order to overcome the current state of “national neglect”, a more serious institutional approach is necessary when it comes to developing and nurturing a culture of memory related to the “Košare” and their shaping as an identity element. This implies a strategic approach to creating public policies, such as educational, cultural and other types of practical policies that can contribute in this field. Further, special attention is paid to the education and upbringing system as a key factor in this process. It is also pointed out the role that the media and media memory policies can play in this. In terms of the methodological framework, the method of content analysis of relevant scientific and professional, as well as media and certain legal documents has been applied. The subject of the analysis is also some literary works of importance for understanding and explaining the symbolism of “Košare”. Also, testimonies and interviews of members of the Yugoslav Army who were direct participants in the forenamed battles have been used as a source of data. Discursive analysis has been applied as a supplementary method, as well as the observation method, which is indispensable when it comes to contemporary social processes and phenomena that we have the opportunity to witness.
Keywords: Košare; Kosovo and Metohija; symbolism; national identity; Serbia; Yugoslav Army; culture of memory; politics of memory; education; media